HISTORICAL AND GEOGRAPHICAL FEATURES OF THE FORMATION OF UKRAINIAN FOREIGN ENVIRONMENT - Зубик, Андрій (Human Geography Journal, 2015)
The reasons for the mass movement of people are economic hardship, persecution for political opinions, and membership of a particular ethnic group or religion. Ukrainians were no exception, and still emigrate in search of a better fate. As a result, in some countries had formed Ukrainian foreign environment. The paper presents a new look at the classification of Ukrainian emigration. Traditionally, there are four so-called «wave» of migration. To the structure of migration added three periods that do not fit into the structure of the so-called «waves» – middle XVII – last quarter of the XIX century, 1914–1917 and 1939–1945. Described the typology of similarity formation Ukrainian foreign environments and migration periods. Found country of destination Ukrainian immigrants into time periods.